TO THE QUESTION OF MODERN DIAGNOSIS AND DEFERENTIAL DIAGNOSIS OF SEVERE DERMATOSES: TOXIC EPIDERMAL NECROLYSIS AND STEVEN-JOHNSON SYNDROME - Tsysnetska Аліна (Actual Problems of Medicine and Pharmacy, 2022)
Recognition of the clinical presentation, correct diagnosis, and differential diagnosis of toxic epidermal necrolysis (TEN) and Steven-Johnson syndrome (SJS) is important due to the rarity of these syndromes and severe life-threatening outcomes. In most cases, the underlying etiology of TEN and SJS is adverse reaction to medication. Diagnosis in the first days of presentation is complicated and reliable laboratory markers are absent. Correct early diagnosis and differential diagnosis are important for hospitalization admission, treatment, life expectancy and subsequent sequelae.